Case study: Nordic Windpower's critical blade failures. (2016) - Bauer, John; Eastham, James
In 2007, the start-up wind turbine generator (WTG) manufacturer, Nordic Windpower, officially launched in North America as a merger between Swedish, USA, and UK development teams. Based on a design researched and funded by the Swedish Government, Nordic Windpower developed the N1000, a two-bladed, 1 MW WTG geared toward the distributed and community wind market. The N1000 was the first utility-scale, two-bladed WTG of its size in North America. Serial production of the N1000 began in 2009, producing a total of eight units. During commissioning, field testing, and after grid production, repeated failures of the fixed-pitch and stall-regulated rotor braking system prevented Nordic Windpower from meeting contractual obligations. On August 28, 2013, Nordic Windpower LLC liquidated the business under Chapter 7. This case study examines Nordic Windpower's critical blade failures from a systems engineering perspective, identifies best practices, and offers potential solutions for Nordic Windpower's development process.